The observation of magnetic excitations in a single layered and a bilayered brownmillerite. - Blundell, S; Stride, J; Brooks, M; Steer, C; Nair, S; Battle, P; Rosseinsky, M (2005)
We describe the results of an inelastic neutron scattering measurement of the magnetic excitations in SrCaGaMnO(5+δ), a quasi-two-dimensional compound whose structure consists of layers of MnO(6) octahedra separated by layers of GaO(4) tetrahedra (the brownmillerite structure), and Ca(2.5)Sr(0.5)Mn(2)GaO(8), a bilayered brownmillerite. In both materials, a band of magnetic scattering appears below the magnetic ordering temperature which can be associated with magnon excitations. Our measurements allow us to provide an estimate for the intraplane exchange constant in both materials, which we find to be 3.4(4) meV for SrCaGaMnO(5+δ) and 2.2(4) meV for Ca(2.5)Sr(0.5)Mn(2)GaO(8).